2010
DOI: 10.1007/s00421-010-1352-7
|View full text |Cite
|
Sign up to set email alerts
|

No effect of skin temperature on human ventilation response to hypercapnia during light exercise with a normothermic core temperature

Abstract: Hyperthermia potentiates the influence of CO(2) on pulmonary ventilation (.V(E)). It remains to be resolved how skin and core temperatures contribute to the elevated exercise ventilation response to CO(2). This study was conducted to assess the influences of mean skin temperature (_T(SK)) and end-tidal PCO(2) (P(ET)CO(2)) on .V(E) during submaximal exercise with a normothermic esophageal temperature (T(ES)). Five males and three females who were 1.76 +/- 0.11 m tall (mean +/- SD), 75.8 +/- 15.6 kg in weight an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The temperature of the human body is dependent on a number of variables, but there is a significant difference between the temperature of the skin (∼32-36°C) and the body core (∼37-40°C) (19,20). TS viral vaccines, such as FluMist, take advantage of the anatomical differences in human body temperatures (11,13,14).…”
Section: Resultsmentioning
confidence: 99%
“…The temperature of the human body is dependent on a number of variables, but there is a significant difference between the temperature of the skin (∼32-36°C) and the body core (∼37-40°C) (19,20). TS viral vaccines, such as FluMist, take advantage of the anatomical differences in human body temperatures (11,13,14).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, our findings suggest that changes in skin temperature have no effect on the ventilatory response to increasing body temperature during moderate intensity exercise 3) . Similarly, Greiner et al 23) reported that changes in skin temperature do not influence ventilation during light intensity exercise. And, whereas hypohydration attenuates the cutaneous vasodilatory response and sweating 24,25) , we found that hypohydration (2.5% of body weight) does not influence hyperthermia-induced hyperventilation, though the Tes threshold for cutaneous vasodilation is increased, and the sensitivity of cutaneous vasodilation is reduced 11) .…”
Section: Characteristics Of Hyperthermia-induced Hyperventilationmentioning
confidence: 99%
“…In accordance with the above mentioned facts, the human body temperature varies depending upon the body parts, temperature of the skin varies between 32 and 36°C whereas the body core is about 37–42°C. [78] Over decades, attempts have been made to develop TS bacterial strains and viral strains,[9–12] yet bacterial strains were not adapted for human vaccination,[13] for example, the TS version of Yersinia pestis [14] and because of their reversion this strain was not further developed. [13] Further, small numbers of TS bacterial strain vaccines (developed by chemical mutagenesis) were developed for veterinary use; but it is uncertain whether the TS nature is primary attenuating phenotype or merely a coincidental phenotype.…”
mentioning
confidence: 99%